FOSTERING PROSPECTIVE TEACHERS' COGNITION IN EFL TEACHING PRACTICUM THROUGH REFLECTIVE TEACHING - Yenni Rozimela; Yuli Tiarina (Universitas Negeri Padang, 2015)
This article presents a partial result ola study conducted to look at the implementation of reflective teaching to improve the prospective teachers' teaching skill in teaching EFL. The focus reported here is their selfreflection which unveils their cognition of teaching English. Twelve prospective teachers taking teaching practicum subject at five junior high schools in Padang were involved. They were required to write the results of their reflection after each teaching presentation in their journals. A focus group interview was then conducted to find out the reasons behind their self-evaluation and their view about the interconnectedness between what they had learned about teaching and what they experienced in the field. The results of the analysis of these two sets of data revealed that the prospective teachers' reflection was dominated by their difficulties dealing with classroom management. Thus, they did not really give sufficient attention to othe aspects of teaching of which they had strengths and weaknesses. In ihe interview it was found that they were aware oftheir strengths and weaknesses of other aspects of teaching, but they thought that their instructional plans were profoundly influenced by their classroom management. An essential conclusion to draw is that prospective teachers should be provided with theory, strategies, and tips with regards to classroom management.